The Lived Experience of Patients with Diabetes Mellitus Participating in Rubber Ball Foot Exercise Intervention: A Qualitative Study Using Interpretative Phenomenological Analysis - Abdurrasyid Abdurrasyid; Rian Adi Pamungkas; Yunata Kandhias; Fransiskus Febri Juferta; Puspita Dwi Anggraeni; Ratu Dini; Ida Farida; Siti Hairunnisa (Yayasan Ahmad Mansyur Nasirah, 2026)
Diabetes mellitus is a chronic condition that requires comprehensive and long-term management, including non-pharmacological interventions that support patients’ quality of life. Rubber ball foot exercise represents a simple, low-cost physical activity designed to enhance peripheral circulation and strengthen lower extremity function. This study aims to explore the lived experiences of individuals with type 2 diabetes mellitus who participated in a structured rubber ball foot exercise intervention. Employing a qualitative approach through Interpretative Phenomenological Analysis (IPA), the study provides an in-depth understanding of participants’ perceptions, emotions, and reflections throughout the intervention process. Findings reveal that the exercise not only offers physiological benefits but also fosters self-confidence, hope, and social connectedness, serving as a meaningful space for psychosocial recovery. Despite practical challenges in home implementation such as limited space, family dynamics, and lack of structured reminders participants demonstrated notable adaptive strategies, including visual cues, family involvement, and spatial modifications. These responses highlight the importance of context-sensitive and participatory design in enhancing program adherence and sustainability. From an economic perspective, the intervention’s affordability, accessibility, and potential for independent practice underscore its relevance for resource-limited settings. Its integration into national programs such as Prolanis and Posbindu PTM may strengthen primary healthcare systems and promote community engagement in chronic disease prevention. Given its clinical efficacy, social relevance, and cost-efficiency, rubber ball foot exercise holds strategic potential as a sustainable, community-based intervention for non-communicable disease control.